Investigating the Use of Dry Matter Intake and Energy Balance Prepartum as Predictors of Digestive Disorders Postpartum - Pérez-Báez, Johanny; Risco, Carlos A.; Chebel, Ricardo C.; Gomes, Gabriel C.; Greco, Leandro F.; Tao, Sha; Toledo, Izabella M.; do Amaral, Bruno C.; Zenobi, Marcos G.; Martinez, Natalia; Dahl, Geoffrey E.; Hernández, Jorge A.; et al. (Frontiers in Veterinary Science, 2021)
One objective was to evaluate the association of dry matter intake as a percentage of body weight (DMI%BW) and energy balance (EB) prepartum and postpartum, and energy corrected milk (ECM) postpatum with digestive disorders postpartum. For this, ANOVA was used, and DMI%BW, EB and ECM were the outcome variables, and left displaced abomasum (LDA), indigestion and other digestive disorders (ODDZ) were the explanatory variables. The main objective was to evaluate prepartum DMI%BW and EB as predictors of digestive disorders. For this, logistic regression was used, and LDA, indigestion and ODDZ were the outcome variables, and DMI%BW and EB were the explanatory variables. Data from 689 cows from 11 experiments were compiled. Left displaced abomasum was not associated with prepartum DMI%BW or EB. Cows that developed LDA had lesser postpartum DMI%BW, lesser postpartum EB, and lesser postpartum energy corrected milk on d 18 and 19 postpartum than cows without LDA. Cows that developed indigestion had lesser prepartum and postpartum DMI%BW and EB than cows without indigestion. Energy corrected milk was not associated with indigestion postpartum. Cows that developed ODDZ had lesser prepartum DMI%BW on d -8 and from d -5 to -2, lesser prepartum EB on d -8 and from d -5 to -2, and lesser postpartum DMI%BW than cows without ODDZ. Each 0.1 percentage point decrease in the average DMI%BW, and each Mcal decrease in the average EB in the last 3 d prepartum increased the odds of having indigestion by 9% each. Cut-offs for DMI%BW and EB during the last 3 d prepartum to predict indigestion were established, and were ≤ 1.3 %/d, and ≤ 0.68 Mcal/d, respectively. In summary, measures of prepartum DMI%BW and EB were associated with indigestion, and ODDZ postpartum and were predictors of indigestion postpartum, although the effect sizes were small.